2019
DOI: 10.1111/ssqu.12629
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Classification Trees to Discern Patterns of Terrorism*

Abstract: Objective. Though applied widely in the fields of medicine, finance, ecology, psychology, and computer science, machine learning algorithmic-based methods are a relatively novel approach to social scientific analysis that have yet to be extensively applied. Yet as we argue in this article, a specific form of algorithmic analysis known as C4.5 classification trees has much to offer social analysis and, specifically, the study of social and political violence. Method. This article describes four novel classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The results of the experiments show that the suggested method can be used to analyze and predict information about terrorist attacks thoroughly and accurately. Saiya et al [36] used a specific kind of algorithmic analysis known as C4.5 classification trees to examine social and political violence. Their proposed method has been applied based on four unique outline techniques for comparing classification models for the C4.5 classification method.…”
Section: A Machine Learning Approach For Enhancing Defense Against Gl...mentioning
confidence: 99%
“…The results of the experiments show that the suggested method can be used to analyze and predict information about terrorist attacks thoroughly and accurately. Saiya et al [36] used a specific kind of algorithmic analysis known as C4.5 classification trees to examine social and political violence. Their proposed method has been applied based on four unique outline techniques for comparing classification models for the C4.5 classification method.…”
Section: A Machine Learning Approach For Enhancing Defense Against Gl...mentioning
confidence: 99%
“…Terrorists, they contend, come in different varieties, have different undergirding ideologies, and use different tactics. The most important distinction between terrorist groups raised in the literature pertains to ideology, especially ideological differences between those groups motivated by religion and those that are not (Fox 2003; Hoffman 1995; Juergensmeyer 2003; Rapoport 1984; Saiya 2015a; Saiya 2018; Saiya and Scime 2019). Various studies have found that religious terrorists–because they hold non-negotiable demands and therefore regard violence as a divine duty–fight harder, last longer, and cause more destruction than their non-religious counterparts (Hassner 2003; Hassner 2009; Henne 2012; Hoffman 1995; Jasko et al 2022; Svensson 2007; Svensson and Harding 2011; Toft 2007).…”
Section: Theorizing the Differential Effects Of Democracy On Terrorismmentioning
confidence: 99%
“…Previous peer-reviewed studies have shown religious freedom to be positively related to a number of public goods, including (i) development (Alon & Chase, 2005;Grim, 2008a;Shah, 2018), (ii) security (Farr, 2008;Toft et al, 2011;Grim & Finke, 2011;Inboden, 2012;Saiya, 2014;Saiya, 2015a;Saiya, 2015b;Saiya and Scime, 2015;Saiya, 2017a;Saiya, 2017b;Saiya and Fidler, 2018;Saiya and Scime, 2019;Saiya, 2019a;Saiya, 2019b;Saiya, 2020;Saiya and Manchanda, 2020a;Saiya and Manchanda, 2020b;Henne, Saiya, and Hand, 2020;Saiya, 2021;Saiya and Hand, 2022;, (iii) business (Grim et al, 2014), and (iv) even health (Grim & Grim, 2019). Thus, religious freedom is believed to not only be an integral part of the "bundled commodity" of human freedoms, it is also closely related to the general betterment of people's lives (Grim, 2008b).…”
Section: Introductionmentioning
confidence: 99%